A review of ethanol wet-bonding: Principles and techniques - Ayar, Muhammet Kerim (European Journal of Dentistry, 2016)
Conventional water wet-bonding technique has been advocated by many scientists, but the excess water will induce suboptimal polymerization of dental adhesives, phase separation, and nanoleakage, which will influence the longevity of resin-dentin interfaces. Recent studies have put forward a new concept, ethanol wet-bonding. This technique can increase in dentin bond durability. This review focuses on the principles of ethanol wet-bonding, its surface treatment methods.
Keywords: Bond strength; dentin; durability; ethanol wet-bonding; wet-bonding